68.5k views
1 vote
Describe the long run behavior: f(t) = (t-4) (t-2)^3 (t-3)^2 A. infinityB. negative infinityC. zeroD. N/A

User Alonblack
by
4.6k points

1 Answer

7 votes

Given:


f(t)=(t-4)(t-2)^3(t-3)^2

Required:

We need to find the long run behavior.

Step-by-step explanation:

Recall that the long-run behavior of a polynomial function is determined by its leading term.

Consider the given polynomial function.


f(t)=(t-4)(t-2)^3(t-3)^2
f(t)=t(1-(4)/(t))t^3(1-(2)/(t))^3t^2(1-(3)/(t))^2
f(t)=t^6(1-(4)/(t))(1-(2)/(t))^3(1-(3)/(t))^2
\text{ The leading term is }t^6
Let\text{ }g(t)=t^6.

Take the limit as infinity.


\lim_(t\to\infty)g(t)=\lim_(t\to\infty)t^6
g(t)\rightarrow\infty\text{ as t approches }\infty

Take the limit as negative infinity.


\lim_(t\to-\infty)g(t)=\operatorname{\lim}_(t\to-\infty)t^6
g(t)\rightarrow\infty\text{ as t approches -}\infty.

Hence we get


f(t)\rightarrow\infty\text{ as t }\rightarrow\text{ -}\infty\text{ and t}\rightarrow\infty

Final answer:

The long run behavior is infinity.

User Menefee
by
5.1k points